Proximity, Family Lore, and False Claims to an Algonquin Identity - Darryl Leroux (Genealogy)
This article examines the type of family lore that leads white Canadians and Americans to claim Indigenous identities. Using a case-study approach, I demonstrate how 2000 descendants of a French-Canadian couple, born in the early 1800s near Montréal, joined one of the largest land claims in Canadian history as “Algonquins”. The tools of critical settler family history provide the necessary theoretical scaffolding to unpack how genealogical and geographical proximity to Indigenous people in the past are the bases for the family lore that propelled these individuals to become card-carrying, voting members of the land claim. Despite continued opposition to their inclusion by the Algonquins of Pikwakanagan First Nation, the only federally recognized Algonquin community involved in the land claim, these fake Algonquins remained potential land claim beneficiaries for over two decades, until an independent tribunal finally removed them in 2023. Family lore resolves the crisis in the family: no longer the colonizers responsible for Indigenous displacement and dispossession, white pretendians become the victims of settler colonial violence.